Penyelundupan Narkotika Di Lembaga Pemasyarakatan - Nadya Riska Wati Rumain; Deassy Jacomina Anthoneta Hehanussa; Julianus Edwin Latupeirissa (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The research of this thesis is that the Correctional Institution or better known as Lapas is a place to foster inmates to become fully human, realize mistakes, improve themselves and not repeat criminal acts so that they can be accepted again by the community. However, ironically, the Penitentiary is used as a place for drug trafficking with various modes of smuggling.Purposes of the Research:  This study aims to analyze and explain the modus operandi of narcotics smuggling in prisons, analyze and explain the prevention of narcotics smuggling in prisons.Methods of the Research: This research uses normative legal research methods, using primary and secondary legal sources, and tertiary and then the data obtained will be presented in a description and given a conclusion.Results of the Research: The results of the research obtained: the modus operandi of smuggling drugs and other prohibited items in correctional institutions (prisons) and detention centers (rutan) has utilized advanced technology, including drones or drones. In addition, the smugglers also use officers, visitors, companion prisoners undergoing assimilation, garbage carts, and goods in the canteen and kitchen to carry out their actions. Prisons and other law enforcement officers must continue to play an active role in seeking preventive and repressive measures to suppress or break the narcotics illicit trafficking network among prisoners because if there is omission, it will result in the ineffective implementation of Law Number 12 of 1995 concerning Corrections and hamper the eradication of criminal acts. Narcotics crime as has been confirmed in the RI Law Number 35 of 2009 concerning Narcotics.